Ring-chain synergy in ionic liquid electrolytes for lithium batteries. Issue 12 (2nd October 2015) - Wu, Feng; Zhu, Qizhen; Chen, Renjie; Chen, Nan; Chen, Yan; Li, Li
Abstract : The ionic liquid-based electrolyte containing ring-like Pyr1, 2O1 TFSI and chain-like DMS exhibits good overall performance in lithium-ion batteries. Abstract : Lithium-ion batteries have been attracting much attention which enables the revolution of wireless global communication. Ionic liquids are regarded as promising candidates for lithium-ion battery electrolytes because they can overcome the limitations of high operating temperatures and flammability concerns of traditional electrolytes. However, at low temperatures they suffer from low ionic conductivity and phase transition. In this paper mixed electrolyte systems are described based on N -methoxyethyl- N -methylpyrrolidinium bis(trifluoromethanesulfonyl)-imide (Pyr1, 2O1 TFSI) and lithium difluoro(oxalate)borate (LiODFB) lithium salt, with ethylene sulphite (ES) or dimethyl sulphite (DMS) as a cosolvent. The mixed electrolyte system exhibits good ion transport properties (a conductivity of 8.163 mS cm −1 ), a wide electrochemical window (5.2 V), non-flammability, the ability to form films to protect the anode and a large operating temperature range (−40 °C to 60 °C). We compare the performance and function of the new mixed electrolyte system with a variety of ionic liquid/cosolvent electrolyte systems developed in previous studies. The ring-chain synergy takes advantage of the availability of both high permittivities based on the ring-like components and low viscosities based on the chain-like components in the mixed electrolyte system and causes the electrolyte to exhibit a good overall performance in safety, ion transport and compatibility with electrodes.